STUDIES ON THE FUNCTION OF INTRACELLULAR RIBONUCLEASES : V. Ribonuclease Activity in Ribosomes and Polysomes Prepared from Rat Liver and Hepatomas - Utsunomiya, Takeshi (The Rockefeller University Press, 1966)
The RNase activity and properties of ribosome and polysome preparations from normal rat liver and some hepatomas have been examined. Polysome and ribosome preparations from the Novikoff, McCoy MDAB, and Dunning hepatomas had considerably higher specific RNase activity than corresponding preparations from normal rat liver, Novikoff ascites, or Morris 5123 hepatomas. The optimum pH of the RNase was approximately 8.5 for all samples tested, and the samples showed no evidence of latent RNase activity when treated with 3 M sodium chloride, EDTA, urea, or p-chloromercuribenzenesulfonic acid. The RNase activity appeared to be associated principally with breakdown products and/or subunits smaller than 80S. In the presence of Mg(++) ions, subunits could reaggregate to form monomer ribosomes indistinguishable from the natural products, but some of the reassociated ribosomes could contain RNase activity which had been bound to the smaller particles. Similar results were obtained with spermine. In the hepatomas, evidence was obtained for the preexistence of considerable amounts of the smaller, RNase-containing subunits in the cell. When a small amount of crystalline bovine pancreatic RNase was added to partly dissociated ribosomes, the RNase was found only in association with the smaller subunits, and little or no enzyme was taken up by ribosomes or polysomes. The results have led to the conclusion that RNase is not a normal constituent of the ribosome or polysome, but that RNase may become associated with these particulates if dissociation and reassociation take place. Some implications of these findings for the stability of messenger RNA and for the mechanism of its breakdown are discussed.